Strategi Rekrutmen Guru: Dilema Kepala Sekolah Antara Perencanaan Kebutuhan Jangka Pendek dan Jangka Panjang - Nasywa, Azzah Iftitachun; Nailati, Izzah; M, Mardiyah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Recruitment is the process of searching for, attracting, and selecting qualified job candidates to fill specific positions within an organization. The recruitment strategy for teachers that school principals face involves balancing short-term and long-term needs. Teacher recruitment is crucial in school human resource management, as it directly impacts the quality of education. The research method used is a literature review, which involves collecting, analyzing, and summarizing relevant literature on teacher recruitment and workforce planning. Literature sources are drawn from journals, books, and academic articles discussing human resource management in education. This study aims to understand the challenges principals face in teacher recruitment and explore applicable strategies. Additionally, the study provides recommendations to assist principals in formulating sustainable recruitment strategies. The research findings show that a combination of short-term and long-term strategies helps maintain both teaching staff stability and educational quality. These recommendations support strategic, flexible recruitment planning and the professional development of teachers to address future challenges.